Reversal of Impaired Hippocampal Long-term Potentiation and Contextual Fear Memory Deficits in Angelman Syndrome Model Mice by ErbB Inhibitors - Kaphzan, Hanoch (2012)
BACKGROUND: Angelman syndrome (AS) is a human neuropsychiatric disorder associated with autism, mental retardation, motor abnormalities, and epilepsy. In most cases, AS is caused by the deletion of the maternal copy of UBE3A gene, which encodes the enzyme ubiquitin ligase E3A, also termed E6-AP. A mouse model of AS has been generated and these mice exhibit many of the observed neurological alterations in humans. Because of clinical and neuroanatomical similarities between AS and schizophrenia, we examined AS model mice for alterations in the neuregulin-ErbB4 pathway, which has been implicated in the pathophysiology of schizophrenia. We focused our studies on the hippocampus, one of the major brain loci impaired in AS mice. METHODS: We determined the expression of NRG1 and ErbB4 receptors in AS mice and wild-type littermates (ages 10-16 weeks), and studied the effects of ErbB inhibition on long-term potentiation (LTP) in hippocampal area CA1 and on hippocampus-dependent contextual fear memory. RESULTS: We observed enhanced neuregulin-ErbB4 signaling in the hippocampus of AS model mice and found that ErbB inhibitors could reverse deficits in LTP, a cellular substrate for learning and memory. In addition, we found that an ErbB inhibitor enhanced long-term contextual fear memory in AS model mice. CONCLUSIONS: Our findings suggest that neuregulin-ErbB4 signaling is involved in synaptic plasticity and memory impairments in AS model mice, suggesting that ErbB inhibitors have therapeutic potential for the treatment of AS.